THE INFLUENCE OF THE DISCRIMINATORY APPROACH ON THE MOBILE AND FLEXIBLE CHARACTERISTICS OF LEARNERS AND THE FACT THAT IT IS A FACTOR OF LOW LEARNING (Web of Teachers: Inderscience Research, 2024)
In this article, the existing discriminatory approach in the education system and its negative impact on students are analyzed as psychological aspects, negative consequences in the preparation of mobile individuals, pedagogical-psychological factors that cause existing problems in the life of society, and social pedagogical-psychological proposals scientific opinions are expressed.